2010
DOI: 10.2217/pgs.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetic and Clinical Factors to Predict Tacrolimus Dose in Renal Transplant Recipients

Abstract: CYP3A5 genotype is the most significant genetic factor that impacts tacrolimus dose among the genes studied. This study generated the first pharmacogenomics model that predicts tacrolimus stable dose based on age, ethnicity, genotype and comedication use. Our results highlight the importance of incorporating both genetic and clinical, demographic factors into dose prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 65 publications
4
29
0
2
Order By: Relevance
“…35 However, Wang and associates found that CYP3A5 genotype is the most significant genetic factor that affects tacrolimus dosage in renal transplant patients. 36 Barrera-Pulido and associates found that in Spanish liver transplant patients, presence of the A allele for the CYP3A5 gene was related to greater requirements of tacrolimus in the early days after transplant. 37 In Chinese liver transplant patients, Weilin and associates, suggested that the recipients' ABCB1 and the donors' CYP3A5 genotype affect the tacrolimus dosage requirements.…”
Section: Discussionmentioning
confidence: 98%
“…35 However, Wang and associates found that CYP3A5 genotype is the most significant genetic factor that affects tacrolimus dosage in renal transplant patients. 36 Barrera-Pulido and associates found that in Spanish liver transplant patients, presence of the A allele for the CYP3A5 gene was related to greater requirements of tacrolimus in the early days after transplant. 37 In Chinese liver transplant patients, Weilin and associates, suggested that the recipients' ABCB1 and the donors' CYP3A5 genotype affect the tacrolimus dosage requirements.…”
Section: Discussionmentioning
confidence: 98%
“…Tacrolimus is a substrate for CYP3A5 and it is well established that individuals carrying one or more *1 alleles have a higher tacrolimus CL and lower trough concentrations [11][12][13][14]17]. Several previous studies have highlighted the differences in CL/F and dose requirements for the CYP3A5*1 carriers compared with individuals with the CYP3A5*3/*3 genotype [24,[30][31][32][33][34]. In a study involving paediatric kidney transplant recipients, tacrolimus CL/F was about 50% higher in children with the CYP3A5*1/*1 or *1/*3 genotype as compared with the CYP3A5*3/*3 genotype [8].…”
Section: Figurementioning
confidence: 99%
“…Some clinical factors and genetic factors play critical roles in determining TAC pharmacokinetics (PK) [9][10][11] . Tacrolimus is known to be transported by P-glycoprotein (MDR1 or ABCB1) and metabolized by cytochrome P450 (CYP) 3A4 and CYP3A5.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports that polymorphisms in genes that participate in the pharmacodynamic (PD) pathway, including IL-2, IL-6, and IL-18, and genes involved in the immune system, for instance TLR4, can influence TAC pharmacokinetics [20][21][22] . The existing algorithms, including genetic and clinical factors, for TAC dose prediction only account for 40% to 60% of TAC dose variations [9,23] . The rest of the variations may be caused by unknown genetic factors that are involved in TAC pharmacodynamics, the immune system, or other related pathways.…”
Section: Introductionmentioning
confidence: 99%